MIGRANT LABOUR PROTECTION IN ASEAN, IN WHAT WAY DOES ILO MATTER? - Sundrijo, Dwi Ardhanariswari; Safitri, Dhanny (Global: Jurnal Politik Internasional, 2023)
Despite the importance of labour migration in Southeast Asia, the mechanism of migrant workers protection in the region is still lacking. Because of that, cases show that often the undocumented and/or the low-skilled workers receive inappropriate treatment in the host countries. In certain cases, they were treated as second-class citizens – this is despite the work that they do. To address these issues, ASEAN has conducted a series of dialog forums and issued various agreements. In doing so, ASEAN have been involving different key stakeholders working on the issue, including international organizations, regional and national civil society organizations, and employers’ union. Unlike mainstream study which mainly focusses on the role of member states or ASEAN in developing regional mechanisms in the region, this research highlights the strategic role of International Labour Organizations (ILO). We argue that ILO is the powerful entities (aside of the member states) behind the region’s decision to pay more serious attention to the issue. This research shows how the ASEAN member states tend to be more open towards ILO’s involvement in their issues – while, because of the region’s norms of non-interference, they usually are reluctant to take any kind of external intervention to the region. Within this context, from the three possible type of roles of international organization in international system proposed by Clive Archer, i.e. as arena, instrument or actor, this article argues that ILO plays a role more as an actor that act independently to fill the gap left by the inability (unwillingness) of ASEAN member state to provide protection to their own migrant workers.